Catching a wave: reclaiming feminism for the 21st century - Dicker, Rory Cooke; Piepmeier, Alison (Northeastern University Press, 2003)
Young women today have benefited from the strides made by grassroots social activists in the 1960s and 1970s, yet they are hesitant to identify themselves as feminists and seem apathetic about carrying the torch of older generations to redress persistent sexism and gender-based barriers. Contesting the notion that we are in a post-feminist age, this collection of essays identifies a third wave of feminism. The contributors argue that the next generation needs to develop a politicized, collective feminism that both builds on the strategies of second wave feminists and is grounded in the material realities and culture of the 21st century. Organized into five sections which mirror the stages of consciousness-raising, the book looks at a broad range of perspectives on the diversity, complexity, multiplicity and playfulness of the third wave. It is also a call to action for new voices to redefine a feminism that is not only personally aware, but also politically involved. (source: Nielsen Book Data)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; féminisme pop; militance; premier cycle; périodes historiques; soc2014; thématiques; transféminisme; troisième vague

Intersexe et transsexualités : Les technologies de la médecine et la séparation du sexe biologique du sexe social - Löwy, Ilana (Cahiers du Genre, 2003)
Le sexe social est construit sur un mode binaire. Par contre, le sexe biologique se présente comme un continuum, avec, aux deux extrêmes, les « sexes biologiques » clairement définis et, au milieu, une large gamme de situations intermédiaires — des individus « intersexe ». De tels individus remettent en cause nos certitudes sur la stabilité des catégories « homme » et « femme ». Cet article trace l’histoire des interventions médicales ayant pour but de corriger l’anomalie de l’intersexe et de produire des êtres humains dont le corps ne remet pas en cause la bipolarité du féminin et du masculin. Il suit les débats sur les liens supposés entre intersexualité et homosexualité puis expose la transition du traitement de l’intersexualité à celui de la transsexualité. Il étudie enfin le rôle des nouvelles techniques de la médecine dans la séparation entre le « sexe » et le « genre ». La possibilité de moduler les paramètres du « sexe biologique » permet alors une réflexion sur le « sexe social » comme variable indépendante des structures biologiques.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme